Role of polyunsaturated fatty acids during infection of Caenorhabditis elegans - Mokoena, Nthabiseng Zelda (University of the Free State, 2023)
During polymicrobial infection, interactions between different microbial species can alter host responses and/or microbial virulence and pathogenesis, often complicating patient treatment and resolution of infection. Polyunsaturated fatty acids (PUFAs) are not only crucial for normal function in mammalian systems, but are also proposed to act as endogenous antimicrobial molecules. Thus, we adopted Caenorhabditis elegans to mimic the Pseudomonas aeruginosa and Candida albicans polymicrobial infections found in humans. We determined the influence of arachidonic acid (AA) and eicosopentaenoic acid (EPA) supplementation on mono- and polymicrobial infection, fatty acid (FA) composition and egg retention of the nematodes, as well as on expression of FA metabolic genes. Supplementation with either AA or EPA in mono- and polymicrobial infections resulted in changes in FA profiles and PUFA biosynthesis pathway. We discovered that the degree of egg retention elicited by C. albicans and P. aeruginosa varied, with C. elegans exposed to both C. albicans and P. aeruginosa showing the highest level of egg retention compared to nematodes infected by either C. albicans or P. aeruginosa alone. Interestingly, the AA supplemented infected nematodes showed an increased level of egg retention, while EPA supplemented infected nematodes showed a significant decrease. Using the C. elegans model, we determined the effects of AA and EPA supplementation on the survival of nematodes with mono- and polymicrobial infection. We showed that the survival of the infected nematodes was influenced by PUFA-supplementation. EPA supplementation effectively reduced C. albicans virulence and inhibited hyphal formation, thus leading to a partial rescue of pathogen susceptibility. However, this was not the case for P. aeruginosa infections. In fact, EPA supplemented nematodes infected with P. aeruginosa were more susceptible. Notably hyphal formation is an important component of Candida pathogenesis in mammals. Furthermore, polymicrobial infection resulted in synergistic virulence. However, C. albicans did not produce any hyphae in the co-infection of either AA, EPA supplemented or unsupplemented nematodes, this suggests that the increase in pathogenesis may be associated with increased P. aeruginosa pathogenesis. To further test the role of EPA in hyphal formation of C. albicans, we hypothesised that cytochrome P450 (CYP450) metabolises EPA to 17,18-epoxyeicosatetraenoic acid (17,18-EpETE), inhibiting C. albicans hyphal formation. We showed that 17,18-EpETE inhibits C. albicans hyphal formation in vitro and in vivo in C. elegans and that inhibitors of mammalian EPA-metabolising CYP450 enzymes, 17-octadecynoic acid (17-ODYA) and 6-(2-propargyloxyphenyl) hexanoic acid (PPOH) restored C. albicans hyphal formation in vivo. Lastly, the role of EPA on the physiology of C. elegans as well as C. albicans in vivo was investigated using gene expression analyses. Among the up-regulated genes, we observed several genes with potential roles in lipid metabolism, hyphal formation, detoxification, stress response and immune response. For instance, we observed an up-regulation of several involved in the synthesis of FAs, including fat-3, fat-4, fat-6, cyp-29A2 and cyp-37A1. Other up-regulated genes were those involved in immune response, such as cyp-37B1, daf-16, fipr-22, ilys-2, lys-5, lys-6, spp-12 and fat-3. Interestingly common genes involved in hyphal formation, such as CAS5, CRZ1, CTA4, ERG11, FCR1, SNQ2, TAC1, TEC1, YOR1 and ZCF3 were also up-regulated. Overall, the benefits of EPA supplementation may be two-fold, by inhibiting virulence factors of C. albicans and stimulating the immune response of the host. Thus, PUFA supplementation might be useful in the treatment of infections in patients caused by C. albicans and P. aeruginosa.

Tydens polimikrobiese infeksies kan interaksies tussen verskillende mikrobiese spesies die gasheer se respons en/of die mikrobe se virulensie en patogenese verander, wat dikwels die behandeling van pasiënte en die oplossing van infeksies bemoeilik. Poli-onversadigde vetsure (POVS’e) is nie slegs noodsaaklik vir normale funksionering in soogdierstelsels nie, maar word ook beskou as potensiële endogene antimikrobiese molekules. Om hierdie rede is Caenorhabditis elegans gebruik om die polimikrobiese infeksies wat deur Pseudomonas aeruginosa en Candida albicans in mense veroorsaak word, na te boots. Ons het die invloed van aragidoonsuur (AS) en eikosapentaenoësuur (EPS) aanvulling op mono- en polimikrobiese infeksies, vetsuursamestelling en eier-retensie van die nematodes, sowel as op die uitdrukking van vetsuur-metaboliese gene, ondersoek. Aanvulling met óf AS, óf EPS tydens mono- en polimikrobiese infeksies het veranderinge in vetsuurprofiele en die POVS-biosintesepad tot gevolg gehad. Daar is bevind dat die graad van eier-retensie deur C. albicans en P. aeruginosa verskil, met C. elegans wat aan beide C. albicans en P. aeruginosa blootgestel is, wat die hoogste vlakke van eier-retensie toon, vergeleke met nematodes wat slegs met een van die twee patogene besmet is. Interessant genoeg het die besmette nematodes wat AS-aanvullings gekry het ’n verhoogde vlak van eier-retensie getoon, terwyl die besmette nematodes met EPS-aanvullings ’n beduidende afname getoon het. Deur die C. elegans-model is die effek van AS- en EPS-aanvulling op die oorlewing van nematodes met mono- en polimikrobiese infeksies bepaal. Die resultate toon dat POVS-aanvulling die oorlewing van besmette nematodes beïnvloed het. EPS-aanvulling het die virulensie van C. albicans doeltreffend verminder en hifevorming geïnhibeer, wat gedeeltelik bygedra het tot die vermindering van patogeen-vatbaarheid. Hierdie effek is egter nie by P. Aeruginosa-infeksies waargeneem nie. Inteendeel, EPS-aangevulde nematodes wat met P. aeruginosa besmet is, was meer vatbaar. Opmerklik is dat hifevorming ’n belangrike komponent van Candida-patogenese in soogdiere is. Verder het polimikrobiese infeksie tot sinergistiese virulensie gelei. Tog het C. albicans geen hife geproduseer in die mede-infeksies van AS-, EPS-aangevulde onaangevulde nematodes nie, wat daarop dui dat die verhoogde patogenese moontlik verband hou met verhoogde P. aeruginosa-patogenie. Om die rol van EPS in die hifevorming van C. albicans verder te ondersoek, is die hipotese gestel dat sitochroom P450 (CYP450) EPS metaboliseer na 17,18-epoksie-eikosatetraenoësuur(“epoxyeicosatetraenoic acid”) (17,18-EpETE), wat hifevorming inhibeer. Ons het getoon dat 17,18-EpETE hifevorming by C. albicans in vitro en in vivo in C. elegans onderdruk. Verder het inhibeerders van soogdier-EPS-metaboliserende CYP450-ensieme, naamlik 17-oktadesinoësuur (“octadecynoic acid” (17-ODYA)) en 6-(2-propargieloksifeniel) heksanoësuur (PPOH) [“6-(2-propargyloxyphenyl”) hexanoic acid (PPOH)], die hifevorming van C. albicans in vivo herstel. Ten slotte is die rol van EPS op die fisiologie van C. elegans sowel as C. albicans in vivo ondersoek deur geenuitdrukkingsanalise. Onder die opgereguleerde gene is verskeie gene geïdentifiseer wat ’n moontlike rol speel in lipiedmetabolisme, hifevorming, detoksifikasie, stresrespons en immuunrespons. Byvoorbeeld, daar is ’n opregulering waargeneem van verskeie gene wat betrokke is by vetsuursintese (VS), insluitend fat-3, fat-4, fat-6, cyp-29A2 en cyp-37A1. Ander opgereguleerde gene was dié wat verband hou met immuunrespons, soos cyp-37B1, daf-16, fipr-22, ilys-2, lys-5, lys-6, spp-12 en fat-3. Interessant genoeg is ook gene wat algemeen met hifevorming verband hou, soos CAS5, CRZ1, CTA4, ERG11, FCR1, SNQ2, TAC1, TEC1, YOR1 en ZCF3, opgereguleer. In die geheel dui die bevindinge daarop dat die voordele van EPS-aanvulling tweeledig mag wees: eerstens deur die inhibering van C. albicans se virulensiefaktore, en tweedens deur die stimulering van die gasheer se immuunrespons. POVS-aanvulling kan dus ’n potensiële rol speel in die behandeling van pasiënte met infeksies wat deur C. albicans en P. aeruginosa veroorsaak word.

Nakong ya tshwaetso ya dikokwanahloko tse ngata, ho sebedisana ha mefuta e sa tshwaneng ya dikokwanahloko ho ka fetola dikarabo tsa moamohedi le/kapa tshwaetso ya dikokwanahloko le pathogenesis, hangata ho thatafatsa phekolo ya mokudi le ho fediswa ha tshwaetso. Diesete tsa mafura a reberebe (di-PUFA) ha di bohlokwa feela bakeng sa tshebetso e tlwaelehileng ditshebetsong tsa diphoofolo tse anyesang, empa hape ho etswa tlhahiso ya hore e sebetse e le dimolekhulo tse sa feleng tsa dikokwanahloko. Kahoo, re ile ra sebedisa manyowa ho etsisa tshwaetso ya dikokwanahloko tse ngata tse bitswang Pseudomonas aeruginosa le Candida albicans tse fumanwang bathong. Re ile ra hlahloba tshusumetso ya tlatsetso ya arachidonic acid (AA) le eicosopentaenoic acid (EPA) ho tshwaetso ya mono- le polymicrobial, sebopeho sa mafura a acid (FA) le ho bolokwa ha mahe a di-nematode, hammoho le ho hlahiswa ha diphatsa tsa lefutso tsa FA. Tlatsetso ya AA kapa EPA ka tshwaetso ya mono- le polymicrobial e bakile diphetoho ho FA profiles le PUFA biosynthesis pathway. Re ile ra fumana hore tekanyo ya ho boloka mahe e bakwang ke C. albicans le P. aeruginosa e a fapana, ha C. elegans e pepesehetse C. albicans le P. aeruginosa e bontsha boemo bo phahameng ka ho fetisisa ba ho boloka mahe ha e bapiswa le dinematode tse tshwaeditsoeng ke C. albicans kapa P. aeruginosa feela. Ho thahasellisang ke hore di-nematode tse nang le tshwaetso tse tlatsitsweng ka AA di bontshitse boemo bo eketsehileng ba ho boloka mahe, ha di-nematode tse nang le tshwaetso tse tlatsitsweng ka EPA di bontshitse phokotso e kgolo. Ha re sebedisa mohlala wa C. elegans, re ile ra fumana hore na ho nwa AA le EPA ho tlatsetsa jwang hore di-nematode tse tshwaeditsweng ke mono le polymicrobial di phele. Re ile ra bontsha hore ho phela ha dinematode tse tshwaeditsweng ho ne ho susumetswa ke ho tlatsetswa ka PUFA. Tlatsetso ya EPA e ile ya fokotsa ka katleho tshwaetso ya C. albicans le ho thibela ho thehwa ha hyphal, ka hona ya lebisa pholosong e itseng ya ho ba le tshwaetso ya pathogen. Leha ho le jwalo, ha ho jwalo ka tshwaetso ya P. aeruginosa. Ha e le hantle, di-nematode tse neng di ena le tshwaetso ya P. aeruginosa tse neng di feptjwa ka EPA di ne di na le tshwaetso e matla. Ka ho qolleha, ho thehwa ha hyphae ke karolo ya bohlokwa ya ho bakwa ha Candida diphoofolong tse anyesang. Ho feta moo, tshwaetso ya dikokwanahloko tse ngata e ile ya fella ka ho bolaya dikokwanahloko ka tsela e dumellanang. Leha ho le jwalo, C. albicans ha ya ka ya hlahisa hyphae leha e le efe ha e tshwaetswa ke di-nematode tsa AA, EPA tse tlatsitsweng kapa tse sa tlatsetswang, sena se fana ka maikutlo a hore keketseho ya pathogenesis e ka amahanywa le keketseho ya P. aeruginosa pathogenesis. E le hore re tswele pele ho hlahloba karolo eo EPA e e phethang ho thehweng ha C. albicans, re ile ra etsa kgopolo ya hore cytochrome P450 (CYP450) e fetola EPA hore e be 17,18-epoxyeicosatetraenoic acid (17,18-EpETE), e thibelang C. albicans ho thehweng ha hyphal. Re bontshitse hore 17,18-EpETE e thibela C. albicans hyphal formation in vitro le in vivo ho C. elegans le hore diahi tsa mammadian EPA-metabodising CYP450 enzymes, 17-octadecynoic acid (17-ODYA) le 6- (((2-propargyloxyphenyl) hexanoic acid (PPOH) di kgutlisitse C. albicans hyphal formation in vivo. Qetellong, ho ile ha hlahlojwa karolo ya EPA mmeleng wa C. elegans hammoho le ya C. albicans in vivo ho sebediswa tlhahlobo ya diphatsa tsa lefutso. Hara diphatsa tsa lefutso tse ntlafaditsweng, re ile ra bona diphatsa tse mmalwa tsa lefutso tse ka nnang tsa eba le karolo ya ho fetola lipid, ho thehwa ha di-hyphal, ho tlosa tjhefo, ho itshwara ha kgatello ya kelello le ho itshwara ha mmele. Ka mohlala, re ile ra bona ho eketseha ha dipalo tsa di-FA tse mmalwa tse amehang ho hlahiseng di-FA, ho akarelletsa le mafura a 3, mafura a 4, mafura a 6, cyp-29A2 le cyp-37A1. Diphatsa tse ding tsa lefutso tse ntlafaditsweng e ne e le tse amehang karabong ya mmele ya ho itshireletsa mafung, tse kang cyp-37B1, daf-16, fipr-22, ilys-2, lys-5, lys-6, spp-12 le fat-3. Ho kgothatsang ke hore diphatsa tsa lefutso tse tlwaelehileng tse amehang ho theha di-hyphal, tse kang CAS5, CRZ1, CTA4, ERG11, FCR1, SNQ2, TAC1, TEC1, YOR1 le ZCF3 le tsona di ne di ntlafaditswe. Ka kakaretso, melemo ya ho nwa di-EPA e ka ba habedi, ka ho thibela disosa tsa C. albicans le ho susumetsa karabelo ya mmele ya ho itshireletsa mafung. Ka hona, ho tlatsetsa ka di-PUFA ho ka ba molemo ho phekola mafu a bakwang ke C. albicans le P. aeruginosa.

Ngesikhathi sokutheleleka ngamagciwane amaningi, ukuhlangana phakathi kwezinhlobo zokuhlaseleka kwamagciwane kungaguqula ukuphendula kowemukelayo futhi/noma ubungozi bezifo zokuhlasela kwamagciwane kanye nezithunywa zobuthi, kujwayele ukwenza isimo ezigolozayo ekwelapheni isiguli kanye nesixazululo sokutheleleka. Izimuncwana ezigcwele ngobuningi bamafutha, amaPolyunsaturated fatty acids (PUFAs) azikho semqoka kuphela ukusebenza kahle ezinqutsheni zezilwane ezincelisayo, kodwa futhi ziyahlongozwa ukuzenza izinhlayiya eziphikisana nokuhlasela kwamagciwane okungapheli. Ngalokho-ke, sisebenzise ama-Caenorhabditis elegens ukulingisa ukutheleleka kokuhlasela kwamagciwane amaningi iPseudomonas aeruginosa kanye neCandida albicans atholakala kubantu. Sithole umthelela wokwengezwa kwe-arachidonic acid (AA) kanye ne-eicosopentaenoic acid (EPA) kokutheleleka okukodwa kanye nokutheleleka kokuhlasela kwamagciwane amaningi, ukwakhekha kwesimuncwana samafutha, ifatty acid (FA) kanye nokugcineka kwamaqanda ezikelemu eziyindilinga, kanye nokuvela kwezakhi zokufuzo lokugaya ukudla ze-FA. Ukwengeza nganoma i-AA noma i-EPA ekuthelelekeni okukodwa kanye nokuhlaseleka ngamagciwane okuningi kube nomphumela ekuguqukeni kwezinhlobo ze-FA kanye nokuhlangana kwemigudu yokuphilayo kwe-PUFA. Sithole ukuthi izinga lokugcineka kweqanda okudalwa ama-C. albicans kanye ne-P. aeruginosa kwehlukahlukene, nama-C. elegans evulelekile kukho kokubili ama-C. albicans kanye ne-P. aeruginosa okuveza izinga eliphezulu lokugcineka kweqanda uma kuqhathaniswa nezikelemu eziyindilinga ezitheleleke ngama-C. albicans noma i-P. aeruginosa khona kodwa. Okumangazayo, izikelemu eziyindilinga ezengezwe ngamagciwane e-AA zaveza izinga elenyukile lokugcineka kweqanda, ngesikhathi izikelemu eziyindilinga ezengezwe ngamagciwane e-EPA zaveza ukwehla okukhulu, ngokusebenzisa imodela ye-C. elegans, sathola imithelela yokwengezwa kwe-AA kanye ne-EPA ekuphileni kwezikelemu eziyindilinga ezinokutheleleka okukodwa kwamagciwane kanye nokutheleleka okuningi. Siveze ukuthi ukuphila kwezikelemu eziyindilinga ezithelelekile kwakunomthelela wokwengezwa kwe-PUFA. Ukwengezwa kwe-EPA kwelekelela ukuncipha kobungozi bezifo zama-C. albicans futhi kwavimba ukwakheka kwemicu yezikhunta, lokho-ke okuholela ekusindiseni okuyingxenye kokuba sengozini kwamagciwane. Nokho-ke, akubanga njalo ngokutheleleka nge-P. aeruginosa. Eqinisweni, izikelemu eziyindilinga ezengezwe nge-EPA ezitheleleke nge-P. aeruginosa zazisengozini. Okuqaphelekayo ukwakheka kwemicu yesikhunta kuyingxenye ebalulekile yezithunywa ezinobuthi ze-Candida ezilwaneni ezincelisayo. Okunye futhi, ukutheleleka kokuhlasela kwamagciwane amaningi kwaba nomphumela wokusebenza ndawonye kwamagciwane. Nokho-ke, ama-C. albicans akakhiqizanga eminye imicu yesikhunta ekuthelelekeni okuhambisanayo kwe-AA, i-EPA eyengeziwe noma izikelemu eziyindilinga ezengengeziwe, lokhu kuphakamisa ukuthi ukwenyuka kwezithunywa zobuthi kungase kuhlobane nokwenyuka kwezithunywa zobuthi ze-P. aeruginosa. Ukuvivinya futhi iqhaza lokwakhekha kwemicu yesikhunta se-EPA ekwakhekeni kwama-C. albicans, sahlawumbisela ukuthi icytochrome P450 (CYP450) igaya i-EPA kuya ku-17,18-epoxyeicosatetraenoic acid (17,18-EpETE), ukuvimba ukwakheka kwemicu yesimuncwana sama-C. albicans. Saveza ukuthi i-17,18-EpETE ivimba ukwakheka kwemicu yesikhunta sama-C. albicans engilazini futhi ukuphila kuma-C. elegans futhi okuyizivimbo zokugayeka kwe-CYP450 yokusheshisa kokuhlangana kwe-EPA kwezilwane ezincelisayo, ama-17-octadecynoic acid (17-ODYA) futhi i-6-(2-propargyloxyphenyl) hexanoic acid (PPOH) yabuyisela ukwakheka kwemicu yesikhunta sama-C. albicans kokuphilayo. Okukugcina, iqhaza le-EPA ekusebenzeni komzimba kwama-C. elegans kanye nama-C. albicans kokuphilayo kwahlolwa ngokusebenzisa ukuhlaziya kokuvela kofuzo. Phakathi kofuzo olulawulwa phezulu, sabona ufuzo oluningana namaqhaza olungaba nawo ekugayekeni kwamafutha, ukwakheka kwemicu yesikhunta, ukukhipha ubuthi, ukuphendula ingcindezi kanye nokuphendula amasosha omzimba. Njengokuthi, sabona ukulawuleka okuphezulu kokuningi okubandakanyeka enhlanganiseleni yama-FAs, okubalwa kukho i-fat-6, i-cyp-29A2 kanye ne-cyp-37A1. Olunye ufuzo olulawulwa phezulu ilolo olubandakanyeka ekuphenduleni kwamasosha omzimba, okufana ne-cyp-37B1, i-daf-16, i-fipr-22, i-ilys-2, i-lys-5, i-lys-6, i-spp-12 kanye ne-fat-3. Okujabulisayo, ufuzo oluvamile olubandakanyeka ekwakhekeni kwemicu yesikhunta, olufana ne-CAS5, i-CRZ1, i-CTA4, i-ERG11, i-FCR1, i-SNQ2, i-TAC1, i-TEC1, i-YOR1 kanye ne-ZCF3 nalo lwalawulwa phezulu. Ngokuphelele, imivuzo yokwengezwa kwe-EPA kungaba izigaba ezimbili, ngokuvimba izimo zobungozi besifo zama-C. albicans futhi kugqugquzele ukuphendula kwamasosha omzimba kokwemukelayo. Kanjalo-ke, ukwengezwa kwe-PUFA kunga nomsebenzi omuhle ekwelapheni ukutheleleka ezigulini okubanga ama-C. albicans kanye ne-P. aeruginosa.
Die rol van poli-onversadigde vetsure tydens infeksie van Caenorhabditis elegans
Seabo sa diesete tse mafura tse reberebe nakong ya tshwaetso ya manyowa
Thesis (Ph.D.(Microbiology))--University of the Free State, 2023
Keywords: Polyunsaturated fatty acids (PUFAs); Polymicrobial infections; Microbial interactions; Nematodes; Candida pathogenesis; Gene expression analysis; Eicosopentaenoic acid (EPA) supplementation; Poli-onversadigde vetsure (POVS’e); Polimikrobiese infeksies; Mikrobiese interaksies; Nematodes; Candida-patogenese; Geenuitdrukkingsanalise; Eikosapentaenoësuur (EPS)-aanvulling; Diesete tsa mafura a reberebe (di-PUFA); Polymicrobial infections; Microbial interactions; di-Nematode; Candida pathogenesis; Gene expression analysis; Eicosopentaenoic acid (EPA) supplementation; Izimuncwana ezigcwele ngobuningi bamafutha; Ukuhlaseleka ngamagciwane amaningi; Ukuhlangana kokukuhlaseleka ngamagciwane; Izikelemu eziyindilinga; Izithunywa zobuthi zeCandida; Ukuhlaziya kokuvela kofuzo; Ukwengezwa kwe-Eicosopentaenoic acid (EPA)